Association between Father Involvement and Emotional Development in Early Childhood: A Cross-Sectional Study - Laiya, Fidyawati; Dareda, Kristine; Dwisetyo, Bayu (Bantayang Omni Cendekia, 2026)
Background: Father involvement plays a crucial role in early childhood development, particularly in shaping children’s emotional well-being. However, in many contexts, paternal roles are still limited due to socio-cultural and structural factors, potentially affecting children’s emotional outcomes. Objective: This study aimed to examine the association between father involvement and emotional development in early childhood. Methods: A quantitative cross-sectional study with a correlational design was conducted, which involving 51 fathers who had children aged 4-6 years, selected using purposive sampling. Data were collected using Father Involvement Questionnaire and Early Childhood Emotional Development Questionnaire. Data analysis was performed using univariate and bivariate analysis, with the Spearman Rank correlation test applied to assess the relationship between variables. Results: The findings showed that most fathers had a moderate level of involvement (45.1%) and most children demonstrated moderate emotional development (45.1%). A significant association was found between father involvement and children’s emotional development (p = 0.001), with a moderate positive correlation (r = 0.469). Higher father involvement was associated with better emotional development outcomes among children. Conclusion: Father involvement is significantly associated with emotional development in early childhood. Strengthening paternal roles through increased engagement, emotional support, and participation in daily parenting activities is essential to promote optimal emotional development.